Submerged Fermentation Processes For The Production Of Benzaldehyde By A Locally Isolated Rhizopus sp. D133 [QK896. L415 2005 f rb] [Microfiche 8580]. - Suleiman, Lawan Danjuma (2005)
The study focuses on the selection and production of an almond cherry flavour, benzaldehyde via direct submerged fermentation processes using a locally isolated fungus. Kajian ini memberi tumpuan kepada pemilihan dan penghasilan benzaldehida, sejenis perisa ceri badam, melalui proses pemfermentasian secara langsung dalam kultur tenggelam menggunakan kulat tempatan.